Guidance on how to achieve comprehensible patient information leaflets in four steps - Lampert, Anette; Wien, Katharina; Haefeli, Walter E.; Seidling, Hanna (International journal for quality in health care, 2016)
Comprehensible information leaflets can improve a patient's knowledge. However, in clinical studies leaflets are often introduced without meticulously verifying their comprehensibility. In an attempt to provide a feasible guidance on how to design comprehensible leaflets we complied and evaluated an easy-to-use development procedure.